2019
DOI: 10.32479/irmm.8355
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Job Involvement Between Job Satisfaction and Organizational Commitment in a Small and Medium Sized Business Enterprise

Abstract: The level of competition among companies nowadays have intensified even further. Companies compete not only with domestic entities but with international and global companies as well. In view of this, there is this never-ending pursuit of that competitive advantage a company can utilize to stay at least a step ahead of competition. Many others have looked at developing superior and more technologically advanced products while other have looked in improving their services. But no matter what strategy a company … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…Without a doubt, this was consistent with the definition of continuance commitment whereby it was looking at the perceived cost (both economically and socially) or risk the employees needed to bear to leave the organisation (Allen & Meyer, 1993;Meyer et al, 1989). However, choosing to remain and stay committed did not mean that employees strived to perform better or ever be satisfied with the organisation (Mendoza, 2019). Based on the findings, the overall continuance commitment was high (M = 4.35, SD = .767).…”
Section: Continuance Commitmentsupporting
confidence: 66%
See 4 more Smart Citations
“…Without a doubt, this was consistent with the definition of continuance commitment whereby it was looking at the perceived cost (both economically and socially) or risk the employees needed to bear to leave the organisation (Allen & Meyer, 1993;Meyer et al, 1989). However, choosing to remain and stay committed did not mean that employees strived to perform better or ever be satisfied with the organisation (Mendoza, 2019). Based on the findings, the overall continuance commitment was high (M = 4.35, SD = .767).…”
Section: Continuance Commitmentsupporting
confidence: 66%
“…In relation, it was also found that there is a significant relationship between job satisfaction and organizational commitment with leadership style among university lecturers (Hazriyanto & Ibrahim, 2019;Tatlah, Akhtar, & Hashmi, 2019). Also, it seems that when given autonomy, teachers or employees tend to have higher satisfaction and commitment level (Mendoza, 2019;Saba, 2011;Tatlah et al, 2019).…”
Section: Impact Of Arrogance Leadership On Individuals In Organisationmentioning
confidence: 99%
See 3 more Smart Citations